A Pt(II) Complex with a PNN Type Ligand Dppmaphen Exhibits Selective, Reversible Vapor-Chromic Photoluminescence - Yuanyuan Hu; Jiangyue Wang; David James Young; Hong-Xi Li; Yuxin Lu; Zhi-Gang Ren (Inorganics)
The reaction of PtCl2 with a PNN type ligand dppmaphen (N-(diphenylphosphanylmethyl)-2-amino-1,10-phenanthroline) yielded a new Pt(II) complex [Pt(dppmaphen)Cl]Cl·H2O (1). Upon excitation at 370 nm, compound 1 emits yellow phosphorescence at 539 and 576 nm at room temperature. Exposure of compound 1 to MeOH vapor induces a shift in its emission to 645 nm, which can be attributed to the substitution of MeOH molecules for H2O, resulting in the disruption and reorganization of weak interactions in 1. This response is selective for MeOH and, to a lesser extent, EtOH, the orange photoluminescence recovered in air. The emission change of 1 was reversible and visible to the naked eye.